2020
DOI: 10.1155/2020/7923045
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Visual Performance and Optical Quality with a Rotationally Asymmetric Multifocal Intraocular Lens and an Apodized Diffractive Multifocal Intraocular Lens

Abstract: Purpose. To compare the short-term visual outcomes and intraocular optical performance of a rotationally asymmetric multifocal intraocular lens (MIOL) (SBL-3, Lenstec, Inc., Christ Church, Barbados) and an apodized diffractive MIOL (the Acrysof IQ ResTOR SN6AD1, Alcon Laboratories, Inc., Fort Worth, Texas, United States). Methods. A prospective, comparative, nonrandomized, and single-center study. Sixty-eight age-related cataract patients (81 eyes) after phacoemulsification cataract surgery and in-the-bag MIOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 33 publications
(35 reference statements)
3
10
0
7
Order By: Relevance
“…As for differences in spherical aberrations between both groups, no statistical significance is found (P > 0.05). These outcomes conform to research findings reported by Wang et al 14 This suggests that implantation of a SBL-3 IOL can introduce greater high order aberrations. Through follow-up visits to patients with Lentis Mplus IOL implantation, high intraocular coma is proved among them.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As for differences in spherical aberrations between both groups, no statistical significance is found (P > 0.05). These outcomes conform to research findings reported by Wang et al 14 This suggests that implantation of a SBL-3 IOL can introduce greater high order aberrations. Through follow-up visits to patients with Lentis Mplus IOL implantation, high intraocular coma is proved among them.…”
Section: Discussionsupporting
confidence: 91%
“…Such an outcome is consistent with those reported by Wang. 14 However, van der Linden et al 15 compared the Lentis Mplus with the Restor SN6AD1 IOL. They found that the IOLs achieved comparable distance vision, while the Restor provided better near visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…11,17 Nevertheless, the introduction of intraocular aberration potentially reduces the retinal image quality of rotationally asymmetric MIOL. 10 Similarly, Nio et al 18 discovered that HOA increases the depth of focus and decreases the MTF value at higher spatial frequency. Therefore, we concluded that the increase of intraocular aberration might decrease the MTF value.…”
Section: Discussionmentioning
confidence: 95%
“…The results were consistent with the previous findings of rotationally asymmetric and diffractive MIOL. [10][11][12] Wang etal 10 reported that rotationally asymmetricMIOL (SBL-3) provided better UIVA and wider range of intermediate vision than apodized diffractive MIOL (SN6AD1). Alio et al 11 Defocus curve is an effective method to evaluate the whole visual acuity of MIOL, showing a visual acuity of different defocus levels, with the result being equivalent to the visual acuity of different viewing distances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation